Legal Review of Environmental Law Concerning Illegal Sand Mining - Prastiyo, Laode Agung; Fitri, Winda (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
This research aims to analyze the regulations, enforcement, and legal sanctions related to illegal sand mining in Batam City. Additionally, the study seeks to assess the environmental impact of illegal sand mining activities and evaluate the efforts made by the Batam City Government and law enforcement authorities in combating illegal sand mining practices. A normative juridical approach, particularly the statute approach, is employed in this research. The research methodology involves data collection, examination of legal regulations, doctrines, juridical aspects, and societal norms. The results indicate that authorities with jurisdiction should anticipate potential issues and environmental damage arising from illegal sand mining. Therefore, the protection of the environment and natural resources needs to be strengthened to ensure the safety of Batam City residents. The Batam City Government is expected to take decisive measures to halt illegal sand mining, including the implementation of criminal sanctions and confiscation of tools used by illegal actors in accordance with applicable regulations.